Thinkwell's macroeconomic - Tomlinson, Steven (Thinkwell, 2001)
This digital "textbook" includes CD-ROMs and customized website, as well as suite of web-based tools to track student performance and facilitate class communication. CD-ROM set contains multimedia tutorials, with animation and sound. Customized website contains illustrated notes, interactive exercises with customized feedback, animations, a threaded discussion forum, and broadcast email